2007
DOI: 10.1091/mbc.e06-10-0909
|View full text |Cite
|
Sign up to set email alerts
|

ATF-2 Regulates Fat Metabolism inDrosophila

Abstract: ATF-2 is a member of the ATF/CREB family of transcription factors that is activated by stress-activated protein kinases such as p38. To analyze the physiological role of Drosophila ATF-2 (dATF-2), we generated dATF-2 knockdown flies using RNA interference. Reduced dATF-2 in the fat body, the fly equivalent of the mammalian liver and adipose tissue, decreased survival under starvation conditions. This was due to smaller triglyceride reserves of dATF-2 knockdown flies than control flies. Among multiple genes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 42 publications
5
52
0
Order By: Relevance
“…A recent study has shown that p38-ATF2 signaling leads to the accumulation of stored energy in Drosophila ( 17 ). In the present study, we showed that dGlcT-1 activates p38-ATF2 signaling.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A recent study has shown that p38-ATF2 signaling leads to the accumulation of stored energy in Drosophila ( 17 ). In the present study, we showed that dGlcT-1 activates p38-ATF2 signaling.…”
Section: Discussionsupporting
confidence: 71%
“…3B ) ( 17 ). Increased FAS and decreased PEPCK mRNA expression phenotypes observed in dGlcT-1 knockdown fl ies were similar to that in dATF2 knockdown fl ies.…”
Section: Dglct-1 Interacts With the P38-atf2 Signaling Pathwaysupporting
confidence: 56%
See 1 more Smart Citation
“…A possible reason why insulin and AKH regulatory signals increased simultaneously could be that transgenic flies have a faster metabolism or that these outputs are regulated by peptide synthesis or release. Drosophila PEPCK is involved in gluconeogenesis and glycerogenesis [46]. Interestingly, elevated pepck levels correspond with elevated whole body glucose levels in Rheb and Myc-Rheb expressing flies.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reshef, 2003). Shown previously to be important in fat metabolism in other insects (Okamura et al, 2007), glyceroneogenesis, like gluconeogenesis, is highly regulated by the transcript accumulation of PEPCK. Fold-change increases for PEPCK mRNA in mountain pine beetle larvae during periods of cold exposure were far greater than any other gene investigated within this study, reaching a high of 58.64-fold 18 March.…”
Section: Transcript Accumulation Dynamics Indicate That Glycerol Is Mmentioning
confidence: 94%